Counting Bicycles, Scooters, and Skateboards in Tempe, AZ - Dorian Lemarchand; Deborah Salon; Hue-Tam Jamme; Thomas Czerniawski (Findings)
Accurate counts of active transportation modes are critical to promote sustainable transportation. Most existing counting efforts overlook micromobility modes. We employ wildlife cameras to capture 24-hour counts of bicycle, scooter, and skateboard use at 25 locations in Tempe, Arizona. These data allow us to understand the time, location, and volume distribution of active transportation usage. We find that bicycles represent 66%, scooters 25%, and skateboards 7% of weekday active travel volumes. Bicycle use spreads across the study area and follows a bi-modal commuting pattern, while scooters are used more evenly from morning until midnight but concentrated in the downtown/campus area.